Mental Distress in Persons from Sexual Orientation and Gender Identity Minority Community - Adhikari, Pralhad (Tribhuvan University Journal, 2024)
People of diverse sexual orientation and gender identity (SOGI) community are a minority in the society all over the world including Nepal. They face stigma, prejudice, discrimination, and lack of opportunities in society, and hence are expected to have more mental distress than other persons of binary categories (i.e., male and female), as predicted by minority stress theory. This study aimed to assess the prevalence of depression, anxiety, and stress (common name: psychological distress) among LGBTQI+ persons of Nepal. A survey was conducted among 244 participants (Mage =25.8 years, SD=7.94) using socio demographic questions and the DASS-21. Depression, anxiety, and stress were seen in 75.4%, 85.7%, and 60.2% of SOGI diverse people. Depression, anxiety, and stress correlated significantly with each other but not with age or no. of close friends. Having income and coming out affected depression. Having family’s unconditional support affected stress. Family’s knowing about participants’ SOGI status affected depression and anxiety. The conclusion is that SOGI diverse people have more depression, anxiety, and stress than people from binary categories. Some social factors like having income, getting family support, and opening up about SOGI status are responsible for the mental distress of SOGI minority people. Psychosocial interventions are urgently needed to help the SOGI minority people lessen their mental distress and promote their mental health.